Analisis Kadar Zat Warna Tartrazin pada Makanan dan Minuman dengan Metode Spektrofotometri UV-Vis - Desi Sri Rejeki; Oktariani Pramiastuti; Sherly Septia Pramesti; Muti Aryanti (Jurnal Medika Nusantara, 2024)
Tartrazine is a yellow dye that is included in synthetic dyes. Tartrazine is used to give a yellow color to the product so that it looks attractive. The maximum limit of tartrazine addition set by the Indonesian government is no more than 100 mg / Kg for food and 70 mg / Kg for soft drinks. This study aims to determine the content of tartrazine dye in food and beverage samples. Identification of tartrazine content was carried out qualitatively and quantitatively on 6 samples. The test results were analyzed using One Way-ANOVA. Qualitative identification was carried out by organoleptic testing, dye testing and testing with Thin Layer Chromatography (TLC). The organoleptic results on the 6 samples produced a yellow color with an average sweet fruit aroma. The color test results showed a reddish brown color. In the TLC test with n-butanol eluent: glacial acetic acid: Water (2:2:1) showed the presence of Rf close to standard tartrazine, this was also supported by the presence of a reddish brown mark after being sprayed with FeSO4 spot detector. Quantitative identification with UV-Vis Spectrophotometry produced a maximum wavelength of tartrazine at 427 nm with an average level in sample A of 23.61 mg/Kg, sample B 30.89 mg/Kg, sample C 0.63 mg/Kg, sample D 0.053 mg/Kg, sample E 12.46 mg/Kg and sample F 5.432 mg/Kg. The results of the study showed the presence of tartrazine content in all samples and entered the safe level category according to the specified limits. Data analysis provided significant differences in levels in each sample studied with a value of ? 0.05.